Co-present photo sharing on mobile devices - Ah Kun, Leonard Martin (Department of Computer Science, 2015)
This dissertation researches current approaches to photo sharing. We have found that most current methods of photo sharing are not as compelling as traditional photo sharing - with the increasing in popularity of digital photography, consumers do not print photos as often as before and thus typically require a group display (such as a PC) to view their photographs collectively. This dissertation describes a mobile application that attempts to support traditional photo sharing activities by allowing users to share photos with other co-present users by synchronizing the display on multiple mobile devices. Various floor control policies (software locks that determine when someone can control the displays) were implemented. The behaviour of groups of users was studied to determine how people would use this application for sharing photos and how various floor control policies affect this behaviour.